Effects of fumonisin and Salmonella infection in the expression of Toll-like receptors in chicken ovary - Gkiorsos, V; Michailidis, G; Anastasiadou, M; Giannenas, I (Journal of the Hellenic Veterinary Medical Society, 2022)
Mycotoxins are secondary metabolites produced mainly by fungi that contaminate animal feed and basic food products throughout the world. Currently, more than 500 mycotoxins are reported and one of the most important concern to public health and agriculture is Fumonisin B1 (FB1). FB1, a mycotoxin produced by Fusarium moniliforme, is a contaminant of animal feed with various and complex cellular effects. Although FB1 has been associated with various diseases in animals, to date few studies have been performed to evaluate the endocrine disrupting effects of FB1 and more particularly the effects in the innate immune mechanisms of farm animals and more specifically in poultry species. As the family of Toll-like receptors (TLRs) is one of the key molecules of the innate immune system, the aim of the present study was to evaluate the transcriptional changes of TLRs in the chicken ovary in vivo, in chicks fed with FB1 and in response to Salmonella Enteritidis (SE) infection. RNA was extracted from the ovaries of sexually mature and aged birds, treated with FB1 and SE. Quantitative real-time PCR analysis revealed that FB1 and SE infection resulted in a significant down regulation of 5 TLR genes in the ovary of sexual mature and aged birds. These findings suggest that the mycotoxin FB1 suppresses the innate immune system of the chicken reproductive organs, through alteration in the expression of certain TLR genes.